Preliminary Efficacy of Growth Hormone Therapy in Children With Congenital HeartDisease and Short Stature: A Six-case Report and Literature Review - YANG Xi; LIANG Siyu; LI Qianqian; DU Hanze; SONG Shuaihua; JIANG Yue; MA Huijuan; CHEN Shi; PAN Hui (Xiehe Yixue Zazhi)
Congenital heart disease (CHD) is a congenital malformation resulting from abnormal embryonic development of the heart and great vessels, accounting for approximately 25% of all congenital malformations. Children with CHD are often complicated by short stature. Although surgical treatment can improve their growth and development to a certain extent, some children still experience growth retardation after surgery. Recombinant human growth hormone (rhGH) is the main drug for treating short stature, but its efficacy and safety in the treatment of patients with concomitant CHD warrant further investigation. This article reports six cases of children with CHD and short stature who were treated with rhGH. Through a literature review, we summarize and discuss the therapeutic efficacy, follow-up experiences, and adverse reactions of rhGH treatment, aiming to provide references for clinicians in applying rhGH to treat patients with CHD and short stature.